Girl at war : a novel - Nović, Sara, 1987- (Random House, 2015)
When her happy life in 1991 Croatia is shattered by civil war, ten-year-old Ana Juric is embroiled in a world of guerilla warfare and child soldiers before making a daring escape to America, where years later she struggles to hide her past.